2012
DOI: 10.1080/03003930.2012.666211
|View full text |Cite
|
Sign up to set email alerts
|

Municipal Service Delivery: The Role of Transaction Costs in the Choice between Alternative Governance Mechanisms

Abstract: Service provision by local governments can be delivered using in-house bureaucracies, private firms, and partnerships with other governments or the not-forprofit sector. This production decision has been a major focus of discussion among scholars, practitioners and political agents for the last quarter of a century. The transaction costs framework is an important tool to analyse decisions regarding the production of local services. In this paper, the authors employ this framework to analyse service delivery in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
74
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(85 citation statements)
references
References 43 publications
5
74
1
5
Order By: Relevance
“…The dominant view in public administration literature is that adverse financial situations lead to the adoption of external arrangements rather than in-house hierarchical solutions (López-de-Silanes et al 1997;Dijkgraaf et al 2003;Brown et al 2006, Levin andTadelis 2010). However, some empirical findings suggest that contracting out at the local level may actually be less prevalent if there is financial stress Rodrigues et al 2012). Rodrigues et al (2012) point out that local public sector unions or other interest groups may be especially vigorously opposed to contracting out during economic decline in fiscal crises.…”
Section: Financial Characteristicsmentioning
confidence: 98%
See 2 more Smart Citations
“…The dominant view in public administration literature is that adverse financial situations lead to the adoption of external arrangements rather than in-house hierarchical solutions (López-de-Silanes et al 1997;Dijkgraaf et al 2003;Brown et al 2006, Levin andTadelis 2010). However, some empirical findings suggest that contracting out at the local level may actually be less prevalent if there is financial stress Rodrigues et al 2012). Rodrigues et al (2012) point out that local public sector unions or other interest groups may be especially vigorously opposed to contracting out during economic decline in fiscal crises.…”
Section: Financial Characteristicsmentioning
confidence: 98%
“…For Spanish waste collection, Plata-Díaz et al (2014) confirmed the view that left-wing political parties prefer to use public rather than private waste management forms. Rodrigues et al (2012) extend this analysis by incorporating the issue of political instability. They showed that higher political instability leads to the externalization of services, thereby shifting responsibility to external agents.…”
Section: Political Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Opening up public service delivery to the market has been shaping England and other Western countries for decades (Rodrigues et al, 2012). It is underpinned by public choice theory where the problem is bureaucracy and the solution is competitive pressure.…”
Section: Public Service Delivery In England: a Changing Landscapementioning
confidence: 99%
“…The underlying argument for engaging non-public sector stakeholders in public service delivery is that services will be better, more cost efficient and provide value-for-money. However, there has been little recent research examining how and why this is happening in relation to specific service areas (Rodrigues et al, 2012), such as green and grey infrastructure provision and to what extent the goals of improving quality and enhancing competition have been achieved (recent exceptions include Williams and Thwaites, 2007;Dempsey et al, 2016). It is unclear for example, how past government policy reforms in England which favoured modes of service delivery privatisation such as Compulsory Competitive Tendering, contribute to today's practices (after Bel and Fageda, 2007).…”
Section: Introductionmentioning
confidence: 99%